Epigenetic targeting of bromodomain protein BRD4 counteracts cancer cachexia and prolongs survival. Issue 1 (December 2017) - Segatto, Marco; Fittipaldi, Raffaella; Pin, Fabrizio; Sartori, Roberta; Dae Ko, Kyung; Zare, Hossein; Fenizia, Claudio; Zanchettin, Gianpietro; Pierobon, Elisa Sefora; Hatakeyama, Shinji; Sperti, Cosimo; Merigliano, Stefano; et al.
Abstract Cancer cachexia is a devastating metabolic syndrome characterized by systemic inflammation and massive muscle and adipose tissue wasting. Although it is responsible for approximately one-third of cancer deaths, no effective therapies are available and the underlying mechanisms have not been fully elucidated. We previously identified the bromodomain and extra-terminal domain (BET) protein BRD4 as an epigenetic regulator of muscle mass. Here we show that the pan-BET inhibitor (+)-JQ1 protects tumor-bearing mice from body weight loss and muscle and adipose tissue wasting. Remarkably, in C26-tumor-bearing mice (+)-JQ1 administration dramatically prolongs survival, without directly affecting tumor growth. By ChIP-seq and ChIP analyses, we unveil that BET proteins directly promote the muscle atrophy program during cachexia. In addition, BET proteins are required to coordinate an IL6-dependent AMPK nuclear signaling pathway converging on FoxO3 transcription factor. Overall, these findings indicate that BET proteins may represent a promising therapeutic target in the management of cancer cachexia. Cachexia is a metabolic syndrome leading to muscle and adipose tissue loss in majority of cancer patients. Here the authors show that, in a mouse model, BET inhibitor JQ1 counteracts muscle and adipose tissue wasting tempering cachexia and prolonging survival through a mechanism unrelated to tumour growth.